Targeted modulation of gene expression through receptor-specific delivery of small interfering RNA peptide conjugates - Schenk, Mareike; Mörl, Karin; Herzig, Stephan; Beck-Sickinger, Annette G. (Journal of peptide science, 2024)
Small interfering RNA (siRNA) has emerged as a valuable tool to address RNA interference (RNAi) to modulate gene expression also in therapy. However, challenges such as inefficient cell targeting and rapid degradation in biological systems have limited its success. To address these issues, the development of a receptor-specific shuttle system represents a promising solution. [F7,P34]-NPY analogues were modified by solid-phase peptide synthesis, enabling non-covalent conjugation with siRNA. This modification yielded an efficient siRNA vehicle capable of binding and transporting its cargo into target cells without adversely affecting receptor activation or cell viability. Mass spectrometry and gel shift assays confirmed successful and stable siRNA binding under various conditions. Microscopy experiments further demonstrated the co-internalization of labeled peptides and siRNA in Hepa1c1 cells, highlighting the stability of the complex. In vitro quantitative RT-PCR experiments, targeting the TSC22D4 gene to normalize systemic glucose homeostasis and insulin resistance, revealed a functional peptide-based siRNA shuttle system with the ability to decrease mRNA expression to approximately 40%. These findings strengthen the potential of receptor-specific siRNA shuttle systems as efficient tools for gene therapy that offer a possibility for reducing side effects.